Ambiguitas Kebijakan Pemerintah Daerah atas Pengembangan Karir Guru PAI - Anjani Wira Murti; Deddy Ramdhani (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2023)
This study aims to find out how the career development policy of Islamic Religious Education teachers under the Local government is implemented and what the supporting and inhibiting factors are. This study was conducted by tracing literature sources and tracking related documents. This study shows that the career development policy has been regulated in Law No. 14 of 2005 concerning Teachers and Lecturers and Government Regulation No. 74 of 2005 concerning Teachers, which mandates two streams of coaching and professional development for teachers, namely: first, coaching and professional development including pedagogical, personality, social, and professional competencies. second, coaching and career development, which consists of three domains, namely assignments, promotions, and promotions. The view that Islamic religious education teachers are under the full authority of the ministry of religion is one of the obstacles to policy implementation. While the supporting factors are the existence of clear rules under the regional staffing agency and a religious and socio-political atmosphere that is conducive and safe, So that the local government provides opportunities for PAI teachers to proactively propose activity programs through teachers' working groups (KKG) and subject teachers' meetings (MGMP).